x+y = sum --->
y = sum - x
product = xy = x(sum-x) ------>
x^2 - sum x + product = 0
x = sum/2 ± sqrt[(sum/2)^2 - product]
There are two solutions because interchanging x and y in the solution will yield another solution. This means that you can take:
x = sum/2 - sqrt[(sum/2)^2 - product]
y = sum/2 + sqrt[(sum/2)^2 - product]
sorry, but I don't get it; how can I have two different solutiuons hen I'm only supposed to have one? Still, thanks.
If you have a solution and you interchange x and y then the sum and the poduct are the same, so that's another solution. This means that when we solve for x we get two solutions, the other solution bwing the value for y.
oh, okay, I get it now; thanks!